Metformin: Is it a drug for all reasons and diseases? - Chris R. Triggle (4278688) (2022)
Metformin was first used to treat type 2 diabetes in the late 1950s and in 2022 remains the first-choice drug used daily by approximately 150 million people. An accumulation of positive pre-clinical and clinical data has stimulated interest in re-purposing metformin to treat a variety of diseases including COVID-19. In polycystic ovary syndrome metformin improves insulin sensitivity. In type 1 diabetes metformin may help reduce the insulin dose. Meta-analysis and data from pre-clinical and clinical studies link metformin to a reduction in the incidence of cancer. Clinical trials, including MILES (Metformin In Longevity Study), and TAME (Targeting Aging with Metformin), have been designed to determine if metformin can offset aging and extend lifespan. Pre-clinical and clinical data suggest that metformin, via suppression of pro-inflammatory pathways, protection of mitochondria and vascular function, and direct actions on neuronal stem cells, may protect against neurodegenerative diseases. Metformin has also been studied for its anti-bacterial, −viral, −malaria efficacy. Collectively, these data raise the question: Is metformin a drug for all diseases? It remains unclear as to whether all of these putative beneficial effects are secondary to its actions as an anti-hyperglycemic and insulin-sensitizing drug, or result from other cellular actions, including inhibition of mTOR (mammalian target for rapamycin), or direct anti-viral actions. Clarification is also sought as to whether data from ex vivo studies based on the use of high concentrations of metformin can be translated into clinical benefits, or whether they reflect a ‘Paracelsus’ effect. The environmental impact of metformin, a drug with no known metabolites, is another emerging issue that has been linked to endocrine disruption in fish, and extensive use in T2D has also raised concerns over effects on human reproduction. The objectives for this review are to: 1) evaluate the putative mechanism(s) of action of metformin; 2) analyze the controversial evidence for metformin's effectiveness in the treatment of diseases other than type 2 diabetes; 3) assess the reproducibility of the data, and finally 4) reach an informed conclusion as to whether metformin is a drug for all diseases and reasons. We conclude that the primary clinical benefits of metformin result from its insulin-sensitizing and antihyperglycaemic effects that secondarily contribute to a reduced risk of a number of diseases and thereby enhancing healthspan. However, benefits like improving vascular endothelial function that are independent of effects on glucose homeostasis add to metformin's therapeutic actions. Other Information Published in: Metabolism License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.metabol.2022.155223